2003
DOI: 10.1046/j.1365-2958.2003.03322.x
|View full text |Cite
|
Sign up to set email alerts
|

AraC/XylS family members, HilD and HilC, directly activate virulence gene expression independently of HilA in Salmonella typhimurium

Abstract: SummarySalmonella typhimurium is a Gram-negative enteric pathogen that can infect intestinal epithelial cells and induce inflammation of the intestinal mucosa. These processes are mediated by a type III secretion system (TTSS), which is encoded on Salmonella pathogenicity island 1 (SPI1). Previous studies showed that four SPI1-encoded transcriptional regulators, HilD, HilC, HilA and InvF, act in an ordered fashion to coordinately activate expression of the SPI1 TTSS. HilD and HilC derepress hilA transcription.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 45 publications
7
71
0
Order By: Relevance
“…5). Among the regulatory components, hilC/hilD has been shown to exert its regulatory effect by directly binding to a site upstream of hilAp (15,23,54). We observed under the standard growth condition that hilAp activity remained at the basal level in the HilC Ϫ or HilD Ϫ mutant background, although the defect was more severe in the HilD Ϫ mutant.…”
Section: Stationary Phase Induction Of Hila Under the Standardmentioning
confidence: 77%
“…5). Among the regulatory components, hilC/hilD has been shown to exert its regulatory effect by directly binding to a site upstream of hilAp (15,23,54). We observed under the standard growth condition that hilAp activity remained at the basal level in the HilC Ϫ or HilD Ϫ mutant background, although the defect was more severe in the HilD Ϫ mutant.…”
Section: Stationary Phase Induction Of Hila Under the Standardmentioning
confidence: 77%
“…The expression of hilA and hilD was examined because they encode important positive regulators of the invasive phenotype (6,58). We also examined the expression of hilC, carried on SPI-1, which increases the expression of hilA and activates the expression of the SPI-1 invF operon independently of hilA when overexpressed (1,23,55,58). The sicA gene, which encodes a chaperone, is the first gene in the sic-sip secreted-effector operon located on SPI-1, and its expression pattern should mimic that of hilA (15,16,42).…”
Section: Resultsmentioning
confidence: 99%
“…Each of them binds directly to the hilA promoter and is able to activate its own expression. In fact, HilC, HilD and probably RtsA, act as derepressors of hilA transcription by counteracting the silencing exerted by nucleoidstructuring proteins such as H-NS or Hha (Akbar et al, 2003;Queiroz et al, 2011). The reason why HilC, HilD and RtsA play such an important role in T3SS-1 expression through hilA regulation is that they are at the integration point of a lot of signals that control SPI-1 expression ( Figure 4).…”
Section: Regulation Of T3ss-1 Expressionmentioning
confidence: 99%
“…In this regulatory circuit, it is currently admitted that HilD has a predominant role whereas HilC and RtsA simply act as signal amplifiers. However, it has also been shown that these three regulators are also directly implicated in the regulation of others invasion genes (Akbar et al, 2003;Ellermeier & Slauch, 2004).…”
Section: Regulation Of T3ss-1 Expressionmentioning
confidence: 99%